Tari Jalungmas Cilacap: Representasi Masyarakat Pesisir, Makna, Simbol, dan Refleksi Karakter dalam Perspektif Ekologi - Sudarto Sudarto; Egi Nurholis; Yat Rospia Brata; Dadan Ramdani (Jurnal Artefak, 2025)
Jalungmas dance is a new dance created by the people of Cilacap, Indonesia. This dance is adapted from Jaipong and Calung Banyumasan dances, formed from the cultural background of coastal communities, which not only feature beautiful movements and music, but also contain deep meanings that reflect their lives, values, and characters. The research aims to analyze Jalungmas dance as a representation of coastal communities, uncover the meanings and symbols contained within it, and examine the reflection of character from an ecological perspective. Using qualitative methods and an interdisciplinary approach, including observation, interviews, and documentation studies. The results of the study show that this dance represents the close relationship between the community and its natural surroundings, reflected in the movements, props, and musical accompaniment of the dance. Its meaning encompasses harmony, unity, togetherness, independence, and respect for nature. The symbols used reinforce the community's identity as fishermen. This dance also reflects a resilient, adaptive character that upholds local wisdom in living a life close to the sea. In addition, it represents and reflects a hard-working character that is adaptive to the environment. This dance is a medium for preserving local culture and strengthening identity. The research is expected to provide new insights into understanding dance as a representation of society and preserving a cultural heritage that is rich in meaning and noble values.